Strategia economică și politica consumului - fundamente și corelații - Puwak, Hildegard (Calitatea Vieții, 1990)
One of the conspicuous problems of the social development process is that of motivating the performances assigned by society or the near and distant future. When motivation focuses on people’s needs, aspirations and ideals, the economic strategy becomes one of the most important instruments for reaching the social targets. The economic strategy and its consumption policy need a scientific basis, in order to solve the inherent contradictions and to ensure the rise of the living standard. The study presents the main issues of the above mentioned problems.